Evolution of Direct Marketing Instruments - Niedzielska , Anna (Studia Oeconomica Posnaniensia, 2017)
Direct marketing interpreted as activities and instruments have a set of direct and individualized influence on customers in the aim of creating and satisfying their needs in selling products and services has changed significantly within the last few years. Most of these activities have been transferred from telemarketing and direct mailing to loyalty programs and interactive marketing on the internet. Call centers and infolines are being ousted by Big Data and Marketing Automation. Moreover, social media, Internet communicators and lingubots are increasingly used to contact customers replacing traditional e-mails. The article presents the direction of current direct marketing changes in both theoretical (critical literature analysis) and practical depiction with the example of selected market activities and the results of the author’s own research.